Nama Haram Tapi Produk Halal: Pandangan Dari Perspektif Undang-Undang Malaysia Dan Hukum Islam - Mohd Farhan Md Ariffin; Nurul Syahadah Mohamad Riza; Mohammad Naqib Hamdan; Mohd Shahril Nizam Md Radzi; Nur Najwa Hanani Abdul Rahman; Mohammad Fahmi Abdul Hamid (USIM PRESS, 2024)
Indexed by Scopus